AN ANALYSIS OF PROCEDURES IN TRANSLATING CULTURAL WORDS AND THEIR MEANING SHIFT FOUND IN THE INDONESIAN NOVEL LASKAR PELANGI - Lara Fedora (English Department, Faculty of Humanities, Andalas University, 2015)
This research deals with the cultural words found in the Indonesian novel Laskar Pelangi written by Andrea Hirata, and its translation, The Rainbow Troops by Angie Kilbane. The aim of this research is to find out the procedures which are used in translating the cultural words and to identify the shift in meaning that occurs in translating the cultural words. The research is conducted following the steps proposed by Sudaryanto (1993). In collecting the data, the writer applied ‘’non- participant observational method” and “note- taking” technique. The writer analyzed using translation identity method (Sudaryanto, 1993:13). Translation identity method is a method used to analyze the translation of one language into another language. The writer applies the formal and informal method to present the result of analysis (Sudaryanto, 1988). In analyzing the data, the theory used are from Newmark (1988), Vinay and Darbelnet (1995), Catford (1974) and supported by Baker’s (1992) and Larson’s (1984). The results indicate that there are four categories of cultural words found in novel Laskar Pelangi. The categories are ecology, material culture, social culture, organization, customs, activities, procedures and concept. Then, in translating the cultural words, the translator tend to use cultural equivalence procedure in the translation. Afterwards, there are seven cultural words shifted in meaning in the translation.Keywords: cultural word, meaning shift